IMMUNOHISTOCHEMICAL ASSESSMENT OF SIGNS OF INFLAMMATION OF NASAL AND PARANASAL SINUSES IN ALLERGIC RHINITIS - Ulmasov Alijon Obidovich (International Journal of Innovations in Engineering Research and Technology, 2024)
In this article, the nose and nasal passages in allergic rhinitis about the immunohistochemical evaluation of inflammatory markers of cavities information is provided. Although allergic rhinitis is rarely diagnosed, the incidence rate is stable with the beginning of kindergarten and education begins to rise steadily.